DEEP VEIN THROMBOSIS SEBAGAI MANIFESTASI SINDROMA PARANEOPLASTIK DARI KANKER PARU - Suega, Ketut (journal of internal medicine; Vol. 12, No. 2 Mei 2011, 2012)
Thrombotic event in patient with cancer is a common feature in contrary to the presentation of thombotic disorders that part of para neoplastic syndrome as a solely initial symptom of an occult malignancy. The underlying mechanism that associating between cancer and thrombosis as well as between cancer and paraneoplastic syndrome is not clearly understood yet. One of those cancers that frequently associated with paraneoplastic syndrome is lung cancer. We reported a 46 years old woman that presents initially because of a swollen left leg and tenderness along the leg. Other examinations within normal finding including normal chest x ray. In approximately a year later, the patient experiences disturbing cough with blood streak, accompany with shortness of breath. She was also complaining of sharp chest pain especially when taking a deep breath. After several examinations performed such as bronchoscopy with bronchial washing, transthoracal biopsy, sonographic study, echocardiography, chest CT scan, this patient was finally diagnose of having advanced lung malignancy. Histologic finding was comfirm with adeno carcinoma poorly differentiated. He was treated under 6 concecutive cycles of gemzitabin combined with carboplatin. Despite completed chemotherapy treatment, she became worst and died because of respiratory failure
Keywords: thrombotic event, paraneoplastic syndrome, lung cancer